Spatialising health work in schools – exploring the complex interconnection of space, health, physical education and masculinity. Issue 1 (1st January 2016) - Gerdin, Göran; Ovens, Alan
Abstract : The spaces of schooling are not mere settings or backdrops where students' learning take place, but are implicated in the production of knowledge and identities/subjectivities – spaces embody specific values, beliefs and traditions. In this paper, we draw on visual ethnographic data from an all-boys school in New Zealand to examine how the spaces of schooling and physical education (PE) perform health work in relation to the all-round development of healthy young masculinities. By drawing on a complexivist philosophy, we draw attention to how school policies, spaces, bodies, students, teachers all intersect to provide the boys with a socio-spatial context in which knowledge and learning about healthy young masculinities is constructed. We demonstrate how stereotypical notions of what boys should be doing and what they like doing is, for instance, materialised by the design and provision of schooling and PE as sporting spaces, based on a form of 'healthism', which privileges individualistic notions of health and the assumption that sport=fitness=health. We conclude that although the design and provision of schooling and PE spaces based on healthism is an important source of pleasures for young men, it also reinforces narrowly defined and even problematic forms of healthy young masculinities.